Evaluation of Coronal Micro-Leakage of Fiber Post with Different Luting Cements (In Vitro Study) - Ababakr, Hidayat; Dara H. Saeed (Zanco Journal of Pure and Applied Sciences, 2022)
Background and Objectives: This research’s objective was to analyze coronal micro-leakage of fiber post using the various types of luting cements. Methods: Thirty extracted mandibular single rooted premolars underwent instrumentation with rotary protaper® system and obturated with protaper® gutta-percha and AH-plus® root canal sealer. After being incubated for twenty-four hours, the post space preparation was done through the usage of the Unicore® post drill #2 forming 8mm deep post space and the identical size of Unicore® fiber post #2 was positioned. The samples that went through preparation were arbitrarily placed within three groups representing the three kinds of luting cement (G1: RelyX Unicem, G2: TotalCem, G3: GC Fuji I). Two layers of nail polish were placed upon the root’s surfaces. However, the coronal 2mm was not painted, and the samples were individually placed within 10% black Indian ink dye for the time period of seventy-two hours. The samples underwent rinsing and removal of nail polish, after that the clearing and decalcifying of the samples were performed. One Way Analysis of Variance (ANOVA) used to test any statistically significant difference among the groups also Turkey’s HSD (Honest Significant Difference) post hoc multiple comparison test used for comparison among the groups after using ANOVA test. Results: The results of the present study showed that groups luted with G1 and G2 better coronal sealing than group which luted with G3, which presented that no statistically noteworthy variances were identified among G1 and G2, but substantial variances were present among (G3) further groups. Conclusion: TotalCem ability for coronal sealing surpassed that of RelyX Unicem. References Schwartz RS, Robbins JW. Post placement and restoration of endodontically treated teeth: a literature review. Journal of endodontics. 2004 May 1;30(5):289-301. https://doi.org/10.1097/00004770-200405000-00001 Viguie G, Malquarti G, Vincent B, Bourgeois D. Epoxy/carbon composite resins in dentistry: mechanical properties related to fiber reinforcements. The Journal of prosthetic dentistry. 1994 Sep 1;72(3):245-9. https://doi.org/10.1016/0022-3913(94)90336-0 Vallittu PK. Prosthodontic treatment with a glass fiber-reinforced resin-bonded fixed partial denture: A clinical report. Journal of Prosthetic Dentistry. 1999 Aug 1;82(2):132-5. https://doi.org/10.1016/S0022-3913(99)70145-9 Bae JM, Kim KN, Hattori M, Hasegawa K, Yoshinari M, Kawada E, Oda Y. Fatigue strengths of particulate filler composites reinforced with fibers. Dental materials journal. 2004;23(2):166-74. https://doi.org/10.4012/dmj.23.166 Duarte S, Botta AC, Meire M, Sadan A. Microtensile bond strengths and scanning electron microscopic evaluation of self-adhesive and self-etch resin cements to intact and etched enamel. The Journal of prosthetic dentistry. 2008 Sep 1;100(3):203-10. https://doi.org/10.1016/S0022-3913(08)60179-1 Krämer N, Lohbauer U, Frankenberger R. Adhesive luting of indirect restorations. American Journal of Dentistry. 2000 Nov 1;13(Spec No):60D-76D. Viguie G, Malquarti G, Vincent B, Bourgeois D. Epoxy/carbon composite resins in dentistry: mechanical properties related to fiber reinforcements. The Journal of prosthetic dentistry. 1994 Sep 1;72(3):245-9. https://doi.org/10.1016/0022-3913(94)90336-0 Coleman AJ, Moses MS, Rickerby HH. Macromolecular leakage beneath full cast crowns: A two-year in vitro investigation. The Journal of prosthetic dentistry. 2001 Jan 1;85(1):20-5. https://doi.org/10.1067/mpr.2001.112435 Heling I, Gorfil C, Slutzky H, Kopolovic K, Zalkind M, Slutzky-Goldberg I. Endodontic failure caused by inadequate restorative procedures: review and treatment recommendations. The Journal of prosthetic dentistry. 2002 Jun 1;87(6):674-8. https://doi.org/10.1067/mpr.2002.124453 Baracco B, Fuentes M, Garrido MA, Gonzalez-Lopez S, Ceballos L. ISO/TS 11405: Dental materials-testing of adhesion to tooth structure. ISO/TS 11405: Dental materials-testing of adhesion to tooth structure., 2003. Odontology. 2013 Jul 1;101(2):177-85. Kosti E, Lambrianidis T, Economides N, Neofitou C. Ex vivo study of the efficacy of H‐files and rotary Ni–Ti instruments to remove gutta‐percha and four types of sealer. International endodontic journal. 2006 Jan;39(1):48-54. https://doi.org/10.1111/j.1365-2591.2005.01046.x D’arcangelo C, Zazzeroni S, D’Amario M, Vadini M, De Angelis F, Trubiani O, Caputi S. Bond strengths of three types of fibre‐reinforced post systems in various regions of root canals. International endodontic journal. 2008 Apr;41(4):322-8. https://doi.org/10.1111/j.1365-2591.2007.01367.x Zorba YO, Erdemir A, Turkyilmaz A, Eldeniz AÜ. Effects of different curing units and luting agents on push-out bond strength of translucent posts. Journal of endodontics. 2010 Sep 1;36(9):1521-5. https://doi.org/10.1016/j.joen.2010.04.026 Baldea B, Furtos G, Antal M, Nagy K, Popescu D, Nica L. Push-out bond strength and SEM analysis of two self-adhesive resin cements: An in vitro study. Journal of Dental Sciences. 2013 Sep 1;8(3):296-305. https://doi.org/10.1016/j.jds.2013.01.007 Rahimi S, Oskoee SS, Shahi S, Maljaei E, Abdolrahimi M, Mokhtari H, Kazemi A. In vitro comparison of apical microleakage following canal obturation with lateral and thermoplasticized gutta-percha compaction techniques. African Journal of Biotechnology. 2010;9(48):8235-40. https://doi.org/5897/AJB10.1215 Fox K, Gutteridge DL. An in vitro study of coronal microleakage in root‐canal‐treated teeth restored by the post and core technique. International Endodontic Journal. 1997 Nov;30(6):361-8. https://doi.org/10.1046/j.1365-2591.1997.00093.x Ravanshad S, Khayat A. An in-vitro evaluation of apical seal ability of thermafil obturation versus lateral condensation. Journal of Dentistry of Tehran University of Medical Sciences. 2004;1(4): 48-55. Ravanshad S, Ghoreeshi N. An In vitro study of coronal microleakage in endodontically‐treated teeth restored with posts. Australian Endodontic Journal. 2003 Dec;29(3):128-33. https://doi.org/10.1111/j.1747-4477.2003.tb00536.x Usumez A, Cobankara FK, Ozturk N, Eskitascioglu G, Belli S. Microleakage of endodontically treated teeth with different dowel systems. The Journal of prosthetic dentistry. 2004 Aug 1;92(2):163-9. https://doi.org/10.1016/j.prosdent.2004.05.004 Farhad AR, Elahi T. The effect of smear layer on apical seal of endodontically treated teeth. Journal of Research in Medical Sciences2004. May-June; 9(3):28-31. Kimura Y, Yonaga K, Yokoyama K, Matsuoka E, Sakai K, Matsumoto K. Apical leakage of obturated canals prepared by Er: YAG laser. Journal of endodontics. 2001 Sep 1;27(9):567-70. https://doi.org/10.1097/00004770-200109000-00003 Belli S, Zhang Y, Pereira PN, Pashley DH. Adhesive sealing of the pulp chamber. Journal of Endodontics. 2001 Aug 1;27(8):521-6. https://doi.org/10.1097/00004770-200108000-00006 Zmener O, Banegas G. Comparison of three instrumentation techniques in the preparation of simulated curved root canals. International endodontic journal. 1996 Sep;29(5):315-9. https://doi.org/10.1111/j.1365-2591.1996.tb01391.x Abd El Halim S, Zaki D. Comparative Evaluation of Microleakage Among Three Different Glass Ionomer Types. Operative Dentistry. 2011;36(1):36-42. Sideridou I, Tserki V, Papanastasiou G. Study of water sorption, solubility and modulus of elasticity of light-cured dimethacrylate-based dental resins. Biomaterials. 2003 Feb 1;24(4):655-65. https://doi.org/10.1016/S0142-9612(02)00380-0 Silikas N, Watts DC. Rheology of urethane dimethacrylate and diluent formulations. Dental Materials. 1999 Jul 1;15(4):257-61. https://doi.org/10.1016/S0109-5641(99)00043-3 Tay FR, Loushine RJ, Lambrechts P, Weller RN, Pashley DH. Geometric factors affecting dentin bonding in root canals: a theoretical modeling approach. Journal of endodontics. 2005 Aug 1;31(8):584-9. https://doi.org/10.1097/01.don.0000168891.23486.de Watson TF. Bonding glass-ionomer cements to tooth structure. Advances in glass-ionomer cements. Chicago: Quintessence. 1999:121-36. Sauro S, Watson T, Thompson I, Toledano M, Nucci C, Banerjee A. Influence of air-abrasion executed with polyacrylic acid-Bioglass 45S5 on the bonding performance of a resin-modified glass ionomer cement. European Journal of Oral Sciences. 2012;120(2):168-177. Feilzer AJ, De Gee AJ, Davidson CL. Setting stresses in composites for two different curing modes. Dental Materials. 1993 Jan 1;9(1):2-5. https://doi.org/10.1016/0109-5641(93)90095-8